1999
DOI: 10.1093/fampra/16.5.522
|View full text |Cite
|
Sign up to set email alerts
|

Promoting medical self-care: evaluation of a family intervention implemented in the primary health care by pharmacies

Abstract: Due to the non-randomization procedure, some caution with regard to generalization of the results must be taken, but they are in concordance with established knowledge of the usefulness of medical self-care. The results indicate that a brief intervention for families can change the use of health authorities. It therefore seems meaningful to implement the intervention in a more comprehensive way in the primary health care setting, while at the same time trying to implement it as a large-scale randomized experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This is important if appropriateness of consultation is a more useful indicator of educational success than frequency of consultation (Entwistle et al. 1998, Jewell 1999, Marklund et al. 1999).…”
Section: Study Limitationsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is important if appropriateness of consultation is a more useful indicator of educational success than frequency of consultation (Entwistle et al. 1998, Jewell 1999, Marklund et al. 1999).…”
Section: Study Limitationsmentioning
confidence: 99%
“…1996, Dewey & Hawkins 1998). It has been suggested that education can improve patients’ knowledge and reduce their need for a professional consultation (Buckley & Kemsley 1995, Callery 1997, Gillam & Pencheon 1998, Impicciatore 1998, Marklund et al. 1999, Entwistle & O'Donnell 2000, Kendrick et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations